THE CORRELATION BETWEEN STUDENTS’ READING MOTIVATION, VOCABULARY MASTERY AND WRITING ABILITY IN RECOUNT TEXT - Septika Ariyanti -; Aulia Hanifah Qomar (Premise: Journal of English Education and Applied Linguistics, 2016)
The purposes of this research are to know the correlation between students’ reading motivation and writing ability in recount text, the correlation between vocabulary mastery and writing ability in recount text, the correlation between students’ reading motivation and vocabulary mastery and the correlation between students’ reading motivation, vocabulary mastery, and writing ability in recount text. This research is quantitative research by using correlation method. In taking the sample, the researcher used saturated sampling technique. The amount of the sample are 38 students at third semester of English Study Program in Muhammadiyah University Academic Year 2015/2016. This research instrument were test and questionnaire. The finding showed that there is correlation between students’ reading motivation and writing ability in recount text namely rxy=0,534. Then, there is correlation between vocabulary mastery and writing ability in recount text namely rxy=0,583. After that, there is correlation between students’ reading motivation and vocabulary mastery namely rxy=0,488. Lastly, there is correlation between students’ reading motivation ,vocabulary mastery and writing ability in recount text namely rxy= 0,788.